Comparative Temporal Transcriptome Profiling of Wheat near Isogenic Line Carrying Lr57 under Compatible and Incompatible Interactions - Yadav, Inderjit S.; Sharma, Amandeep; Kaur, Satinder; Nahar, Natasha; Bhardwaj, Subhash C.; Sharma, Tilak R.; Chhuneja, Parveen (Frontiers in Plant Science, 2016)
Leaf rust caused by Puccinia triticina (Pt) is one of the most important diseases of bread wheat globally. Recent advances in sequencing technologies have provided opportunities to analyse the complete transcriptomes of the host as well as pathogen for studying differential gene expression during infection. Pathogen induced differential gene expression was characterized in a near isogenic line carrying leaf rust resistance gene Lr57 and susceptible recipient genotype WL711. RNA samples were collected at five different time points 0, 12, 24, 48 and 72 hours post inoculation (HPI) with Pt 77-5. A total of 3020 transcripts were differentially expressed with 1458 and 2692 transcripts in WL711 and WL711+Lr57, respectively. The highest number of differentially expressed transcripts was detected at 12 HPI. Functional categorization using Blast2GO classified the genes into biological processes, molecular function and cellular components. WL711+Lr57 showed much higher number of differentially expressed nucleotide binding and leucine rich repeat genes and expressed more protein kinases and p athogenesis related proteins such as chitinases, glucanases and other PR protiens as compared to susceptible genotype. Pathway annotation with KEGG categorized genes into 13 major classes with carbohydrate metabolism being the most prominent followed by amino acid, secondary metabolites and nucleotide metabolism. Gene co-expression network analysis identified four and eight clusters of highly correlated genes in WL711 and WL711+Lr57, respectively. Comparative analysis of the differentially expressed transcripts led to the identification of some transcripts which were specifically expressed only in WL711+Lr57. It was apparent from the whole transcriptome sequencing that the resistance gene Lr57 directed the expression of different genes involved in building the resistance response in the host to combat invading pathogen. The RNAseq data and differentially expressed transcripts identified in present study is a genomic resource which can be used for further studying the host pathogen interaction for Lr57 and wheat transcriptome in general.